Indiaas Readiness on Innovation and Economic Growth: A Strategic Analysis (Global Journal of Human-Social Science, 2014)
India enjoys a glorious path of educational excellence right from its ancient age. Nation has shown its supremacy in almost all the major markets of the world in Information and Communication Technology sector especially in the past two decades. Despite the fact that country has several success stories on card, it is still lagging in innovation and requires to excel better to maintain the rhythm of a sustained growth. The present education system, needs to be further strengthened to provide requisite impetuous to produce more number of innovators and also facilitate the creation of the right eco-system. The present study has attempted to understand the policy initiatives of government and other agencies and also study the gap areas to provide suggestive measures for policy makers to create effective manpower motivate and encourage the growth engine of the innovation.
Keywords: innovation; technology